PEMBANGUNAN SEKTOR PENDIDIKAN SEBAGAI PENUNJANG INDEKS PEMBANGUNAN MANUSIA DI KOTA BANDUNG - Dendi Herdiansyah; Poni Sukaesih Kurniati (Jurnal Agregasi : Aksi Reformasi Government dalam Demokrasi, 2020)
The purpose of this research is that the researcher is keen to know that development in the field of education can be a cog in the process of human development that is even better in other words the human development process of higher quality especially in the city of Bandu ng. The method used in this research is qualitative research with a descriptive approach using literature studies. The results showed that in the development of aspects of education as a driving force for the index of human development, it is true that if the level of development of the educational aspects of a region is maximized, the human development index is also considered to be maximal. Thus the impact of this research is the development process of the educational aspects carried out maximally will get maximum results also for the human development index in the city of Bandung.